Wykorzystanie systemów monitorowania otoczenia w dynamicznej adaptacji przedsiębiorstwa do otoczenia - Jelonek, Dorota (The Use of Environment Monitoring Systems in Dynamic Adaptation of Enterprises to Their Environment, 2007)
The adaptation of an enterprise to the changes occurring in its environment, along with the active search for development opportunities in the context of the enterprise's interests and capacities, is becoming a major issue in the contemporary management system. Information Environment Scanning Systems, which monitor the environment and meet the information needs of the management in the decision-making process, may be useful in the enterprise's adaptation activities. The benefits from using the Information Environment Scanning System in the process of adaptation have been presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 239-245